The use of expanded polytetrafluoroethylene (Gore-Tex) in rhinoplasty - İNANLI, SELÇUK (SPRINGER, 2007)
Background: Septal cartilage still is the most appropriate graft material used in rhinoplasty. In traumatic or revision cases, septal cartilage can be insufficient, and the need for an implant material emerges. In this study, the safety and efficacy of polytetrafluoroethylene (Gore-Tex) used as an implant material in nasal dorsal augmentation were assessed. Methods: This study retrospectively reviewed 74 patients who underwent nasal dorsal augmentation with Gore-Tex. Of the 74 patients who underwent rhinoplasty with Gore-Tex for dorsal augmentation from February 1999 to January 2006, 46 (62.2%) represented primary cases and 28 (37.8%) represented revision cases. The patients were followed from 5 to 62 months (average, 28 months) and questioned about cosmetic and functional outcomes. The results were assessed according to patients' charts as well as preoperative and postoperative photographic documentation. Results: There were no complications such as infections, foreign body reaction, extrusions, resorption, or migration, and all the patients were satisfied with their results. Only one case of soft tissue reaction was observed, which lasted for 3 weeks postoperatively. Conclusions: Biocompatibility, ease of use, lack of extrusion or resorption, and low rate of infection make Gore-Tex a good alternative to autogenous tissue. However, long-term success and complication rates still are lacking, and large numbers of patients with longer follow-up periods are required.
Keywords: Gore-Tex; nasal dorsal augmentation; polytetrafluoroethylene; CARTILAGE; IMPLANTS; SURGERY